2022
DOI: 10.1002/cbdv.202101032
|View full text |Cite
|
Sign up to set email alerts
|

Novel N‐(1H‐Pyrazol‐5‐yl)nicotinamide Derivatives: Design, Synthesis and Antifungal Activity

Abstract: To discover more effective antifungal agents, twenty N‐(1H‐pyrazol‐5‐yl)nicotinamide derivatives were designed, synthesized, and structurally confirmed by 1H‐NMR, 13C‐NMR, and ESI‐MS. All target compounds were evaluated for their antifungal activities by mycelia growth inhibition. Preliminary screening results displayed that many of these compounds had good fungicidal activity to S. sclerotiorum and V. mali. Compound B4 exhibited antifungal activity against S. sclerotiorum and V. mali with EC50 values of 10.35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…According to literature methods, the syntheses of intermediates 3 , 4 , 5 , 6 , and 7 were achieved by utilizing acetonitrile and a substituted ethyl acetate as starting materials. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to literature methods, the syntheses of intermediates 3 , 4 , 5 , 6 , and 7 were achieved by utilizing acetonitrile and a substituted ethyl acetate as starting materials. …”
Section: Methodsmentioning
confidence: 99%
“…Recently, our research team synthesized a variety of pyrazol-5-yl-benzamide derivatives as potential SDHIs through scaffold hopping and reversing the directionality of amide groups of pyrazole-4-carboxamides (Figure ). In this work, pyrazol-5-yl-benzamide derivatives were used as lead compounds, and a novel series of pyrazol-5-yl-phenoxybenzamide derivatives were designed and synthesized by replacing the phenyl ring with a diphenyl ether pharmacophore, aiming to identify more potent SDHIs. The target compounds were evaluated for their in vitro fungicidal activities against six common plant pathogenic fungi/oomycete species, followed by an analysis of the resulting structure–activity relationships.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, our team reported that nicotinamide (4, Vitamin B3) showed moderate antifungal activity against C. albicans, including fluconazole-resistant isolates [10]. More recently, Wang and his co-workers also reported several nicotinamide derivatives (6) exhibiting good fungicidal activities after modification of the boscalid structure [11].…”
Section: Introductionmentioning
confidence: 99%
“…As an important class of heterocyclic derivatives, nicotinamide analogues play an important role in the development of antifungals [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Despite the development and commercialization of several nicotinamide analogues, most have been studied as pesticides ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cinnamamide is a key functional group, working synergistically with the morpholine backbone to ultimately screen out the active molecules. In addition, nicotinamide derivatives exhibit a wide range of pharmacological activity and have been used to develop novel drugs. , For example, the nicotinamide skeleton has been widely used as a versatile pharmacophore in agrochemicals, including boscalid (fungicide), diflufenican (herbicide), and flonicamid (insecticide) (Figure B). These findings suggested the potential of cinnamamide and nicotinamide derivatives as novel fungicides against agricultural pathogens.…”
Section: Introductionmentioning
confidence: 99%